Core Fucosylation of Intestinal Epithelial Cells Protects Against Salmonella Typhi Infection via Up-Regulating the Biological Antagonism of Intestinal Microbiota - Hao, Sijia; Fan, Qingjie; Bai, Yaqiang; Fang, Hui; Zhou, Jiaorui; Fukuda, Tomohiko; Gu, Jianguo; Li, Ming; Li, Wenzhe (Frontiers in Microbiology, 2020)
The fucosylated carbohydrate moieties on intestinal epithelial cells (IECs) are involved in the creation of an environmental niche for commensal and pathogenic bacteria. Core fucosylation catalyzed by fucosyltransferase 8 (Fut8) is the major fucosylation pattern on the N-glycans of the surface glycoproteins on IECs, however, the role of IECs core fucosylation during infection remains unclear. This study was conducted to investigate the interaction between IECs core fucosylation and gut microbiota, and the effects of this interaction on protecting Salmonella enterica subsp. enterica serovar Typhi (S. Typhi) infection. Firstly, the Fut8+/+ and Fut8+/- mice were infected with S. Typhi. The level of IECs core fucosylation and protein expression of intestinal mucosa were then detected by LCA blot and Western blot, respectively. The gut microbiota of Fut8+/+ and Fut8+/- mice before and after S. Typhi infection was assessed by 16S rRNA sequencing. Our results showed that core fucosylation was ubiquitous expressed on the intestinal mucosa of mice and had significant effects on their gut microbiota. Fut8+/- mice was more susceptive to S. Typhi infection than Fut8+/+ mice. Interestingly, infection of S. Typhi upregulated the core fucosylation level of IECs and increased the abundances of beneficial microorganisms such as Lactobacillus and Akkermansia spp. Further in vitro and in vivo studies demonstrated that Wnt/β-catenin signaling pathway mediated the elevation of IECs core fucosylation level upon infection of S. Typhi. Taken together, our data in this study revealed that the IECs core fucosylation plays an important role in protecting against S. Typhi infection via up-regulating the biological antagonism of intestinal microbiota. IMPORTANCE In this study, the importance of epithelial core fucose was explored through studies of mucosal surface-microbe interactions. We provide the first confirmation that the defective of Fut8 gene in mice resulted in susceptibility to S. Typhi infection, and the Wnt/β-catenin pathway is involved in the activation of Fut8 transcription in IECs.